Causes and prevention of Iatrogenic fistula during Gynaecologic Surgery - Sharma, Ashudeep (Nepal Journal of Obstetrics and Gynaecology, 2018)
Pelvic surgery is most common cause of iatrogenic ureteral injury. The incidence of ureteric range from 0.2 to 1% during various gynaecological procedure including laparoscopic surgery. The majority of ureteral injury has no identifiable predisposing factor and occurs more frequently for procedure forbenign lesion. Two third of injury are diagnosed postoperative period. When the injury is recognized intra-operatively, the lesion can be repaired immediately with minimal risk of long term sequelae. Urological injuries to urinary bladder & ureter- uncommon but important. Surgical complications during various obstetric & gynecological open and laparoscopic procedures. One of the important factors is anatomic proximity of ureters & bladder to genital tract. Bladder injuries- most frequent urologic injury. Bladder injuries usually recognized and repaired immediately, and potential complications are typically minor. But ureteral injuries(70%) typically are not recognized immediately & can lead to long term complications. Risk factors are Enlarged uterus, Previous pelvic surgery or radiation, Advanced malignancy Endometriosis, PID ,Pelvic adhesions, distorted pelvic anatomy. Iatrogenic urologic injuries can be prevented by adequate pre-operative assessment, good surgical technique, and visualization of the bladder & ureters. Anticipation and high index of suspicion, early urological referral, and appropriate investigation of suspected urologic injury is of paramount importance. Post-operatively they may present with fever, flank pain and tenderness, oligouria, anuria, uremia, ileus, peritonitis, urinary leakage and hematuria depending upon severity of injury. To prevent ureteral injury surgeon must have thorough knowledge of anatomy and location of ureter during various gynaecological procedure and the specific sites where it is most susceptible to injury.